The Outsourcing of Ethical Thinking. (May 2018) - Nordenhaug, Erik; Simmons, Jack
The teaching of professional rules, procedures and standards, as well as the existence of ethics committees and legal advisers to achieve desired behaviours for a given profession, produces an unforeseen by-product of altering the way individuals relate to ethics. The institutionalization of a moral voice, a kind of artificial conscience for the legally defined 'artificial person', tends to do the ethical thinking for the individual who thinks being moral means methodically following the professionally approved rules. Professionalism and the type of methodological reason it requires are becoming a substitute for internal moral reasoning and personal responsibility, despite the belief that we are becoming more morally responsibly through professional behaviour.